Faktor yang Mempengaruhi Ekspor Minyak Kelapa Sawit Indonesia: Penerapan Model SEM-PLS - Dian Nur Kholis; Deky Aji Suseno (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2025)
Palm oil is one of Indonesia's leading export commodities (GPKI, 2023). The superiority of palm oil commodities is the basis of the research, supported by the Heckser-Ohlin theory of comparative advantage of commodities. This study aims to structurally analyze the influence of world average GDP, exchange rates, production and inflation on Indonesian palm oil exports. Data testing uses the SEM-PLS (Structural Equation Modeling - Partial Least Square) method using WarpPLS 8.0. The data in this study uses secondary data obtained from world average GDP data, exchange rates, production and inflation sourced from the Central Statistics Agency (BPS), Bank Indonesia, and the Worldbank in the form of monthly data for 2018-2023. The results of the study show that world average GDP, production and inflation have a positive effect while the exchange rate has a negative effect on Indonesian palm oil exports. Furthermore, world average GDP and exchange rates have a positive effect while production has a negative effect on Indonesian inflation.